Analysis of EORTC-1219-DAHANCA-29 trial plans demonstrates the potential of knowledge-based planning to provide patient-specific treatment plan quality assurance. (January 2019) - Tol, Jim P.; Dahele, Max; Gregoire, Vincent; Overgaard, Jens; Slotman, Ben J.; Verbakel, Wilko F.A.R.
Highlights: Substantial variations in DAHANCA trial treatment plan quality. Knowledge-based planning can provides automatic patient specific quality assurance. Replanning suboptimal plans substantially lower OAR doses. Abstract: Introduction: Radiotherapy treatment plan quality can influence clinical trial outcomes and general QA may not identify suboptimal organ-at-risk (OAR) sparing. We retrospectively performed patient-specific quality assurance (QA) of 100 head-and-neck cancer (HNC) plans from the EORTC-1219-DAHANCA-29 study. Materials and methods: A 177-patient RapidPlan (Varian Medical Systems) model comprising institutional HNC plans was used to QA trial plans (Ptrial ). RapidPlan plans (Prapidplan ) were created using RapidPlan and Eclipse scripting to achieve a high degree of automation. Comparison between Prapidplan mean predicted/achieved OAR doses, and Ptrial mean OAR doses was made for parotid/submandibular glands (PGs/SMGs) and swallowing muscles (SM). Results: OAR predictions were made within 2 min per patient. Averaged PG/SMG/SM mean doses were 2.0/9.0/3.8 Gy lower in Prapidplan . Using predicted Prapidplan combined mean OAR dose as the benchmark, a total of 60/27/4 trial plans could be improved by 3/6/9 Gy respectively. Discussion: Individualized QA indicated that OAR sparing could frequently be improved in EORTC-1219 study plans, even though they met the trial's generic plan criteria. Automated, patient-specific QA can be performed within a few minutes and should be considered to reduce the influence of planning variation on trial outcomes.